High prevalence of circulating autoantibodies against thyroid hormones in vitiligo and correlation with clinical and historical parameters of patients. (1st October 2014) - Colucci, R.; Lotti, F.; Dragoni, F.; Arunachalam, M.; Lotti, T.; Benvenga, S.; Moretti, S.
Summary: Background: Autoantibodies against thyroid hormones (THAbs) directed towards triiodothyronine (T3‐Ab) and/or thyroxine (T4‐Ab) are very rare in the general population. They are increased in some nonthyroidal autoimmune diseases, where they seem to predict autoimmune thyroid disorders (ATDs). So far, their presence in patients with vitiligo has not been evaluated, but it might have a possible predictive role. Objectives: To assess the prevalence of THAbs in a group of vitiligo patients and to correlate their presence with clinical and historical parameters. Methods: In total 79 patients with nonsegmental vitiligo and 100 controls were examined. Clinical characteristics of vitiligo and family and personal medical history were evaluated. Antinuclear autoantibodies, thyroid hormones and thyroid autoantibodies were measured. IgM T3‐Ab, IgG T3‐Ab, IgM T4‐Ab and IgG T4‐Ab were assayed by a radioimmunoprecipitation technique. Fisher's test, Student's t ‐test and χ 2 ‐test were used for statistical analysis. Results: Overall 77 of 79 patients (97%) had at least one type of THAb (11 T3‐Ab, 10 T4‐Ab, 56 both). In the control group, only one person (1%) had THAbs. In patients with vitiligo, T3‐Abs were significantly associated with leucotrichia (IgM+IgG, P = 0·033; IgG, P = 0·039; IgM, P = 0·005) and thyroglobulin autoantibodies (IgM+IgG, P = 0·031; IgG, P = 0·058), while the absence of T3‐Ab was related to personal history of cancer (IgM+IgG, P = 0·021; IgG, P = 0·039). T4‐Abs were significantly associated with vitiligo activity (IgM+IgG, P < 0·001; IgM, P = 0·037) and duration (IgG, P = 0·013). Conclusions: The surprisingly high prevalence of THAb in patients with vitiligo and their associations suggest a possible pathogenetic role in the disease and stress the tight link between vitiligo and ATDs. Further evaluation in a larger group of patients and an adequate follow‐up are needed to define their potential predictive role.